IMPLEMENTATION OF MADRASAH DIGITAL REPORT APPLICATION IN DEVELOPMENT EDUCATION MANAGEMENT INFORMATION SYSTEMS AT MTs. HIDAYATULLAH LOPI SINJAI REGENCY - Br, A. Nurhidayah; Palangkey, Rahmi Dewanti; Bakri, Muhammad Ali (Universitas Islam Negeri Alauddin Makassar, 2024)
This research discusses the implementation of madrasah digital report applications in development education management information systems at MTs. Hidayatullah Lopi. This study is a descriptive qualitative research. Data collection instruments include observation, interviews, and documentation. Informants in this study are vice principals of the madrasah, RDM operators, class guardians, and subject teachers. The research findings reveal that the madrasah digital report is a policy of the Ministry of Religious Affairs of the Republic of Indonesia as a form of digitization development in Madrasah. This RDM application is a transformation from manual reports, consisting of planning, implementation, and evaluation stages. Its advantages include enhancing the effectiveness of student report processing, but its weakness lies in the inability to be accessed remotely from the server.